New Evidence on the Location and Nature of Iron Age, Persian and Early Hellenistic Period Jerusalem - Shalev, Yiftah 19XX- (Tel Aviv, 2020)
The article presents finds unearthed during the renewed excavations at the Giv>ati Parking Lot in the ‘City of David’, Jerusalem. The finds, which date from the late Iron Age to the Persian and Early Hellenistic periods, testify to the importance of the western slope of the City of David ridge in the city’s urban development. When water was transferred from the Gihon Spring to the Siloam Pool the significance of the rugged eastern slope of the ridge was reduced. As a result, the western slope was adapted for public construction. After the 586 BCE destruction, the city was rebuilt along the summit of the ridge and on the northwestern slope.